A comparison of on-ice external load measures between subelite and elite female ice hockey players - Douglas, A. S.; Rotondi, M. A.; Baker, J.; Jamnik, V. K.; Macpherson, A. K. (The Journal of Strength and Conditioning Research, 2022)
This study quantified and examined differences in measures of on-ice external load for subelite and elite female ice hockey players. External load variables were collected from subelite (N = 21) and elite (N = 24) athletes using Catapult S5 monitors during the preseason. A total of 574 data files were analyzed from training and competition during the training camp. Significant differences between groups were found across all variables. Differences in training between the 2 groups ranged from trivial (forwards PlayerLoad, p = 0.03, effect-size [ES] = 0.18) to large (forwards Explosive Efforts [EEs], p < 0.001, ES = 1.64; defense EEs, p < 0.001, ES = 1.40). Match comparisons yielded similar results, with differences ranging from small (defense Low Skating Load [SL], p = 0.05, ES = 0.49; Medium SL, p = 0.04, ES = 0.52) to very large (forwards PlayerLoad, p < 0.001. ES = 2.25; PlayerLoad·min-1, p < 0.001, ES = 2.66; EEs, p < 0.001, ES = 2.03; Medium SL, p < 0.001, ES = 2.31; SL·min-1, p < 0.001, ES = 2.67), respectively. The differences in external load measures of intensity demonstrate the need to alter training programs of subelite ice athletes to ensure they can meet the demands of elite ice hockey. As athletes advance along the development pathway, considerable focus of their off-ice training should be to improve qualities that enhance their ability to perform high-intensity on-ice movements.